2005
DOI: 10.1177/1049732305277860
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Evidence of Psychosocial Thriving in Childhood Cancer Survivors

Abstract: Advances in medical treatment for childhood cancer have resulted in dramatically increased survival rates and a growing population of long-term survivors. Until recently, researchers reported primarily negative psychosocial sequelae of childhood cancer. Emergent conceptual frameworks propose that the assumption of pathology or long-term deficits in functioning might obscure an understanding of the full range of outcomes. Using qualitative interview data (N = 50), the authors explore how cancer can lead to posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
141
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(157 citation statements)
references
References 53 publications
12
141
0
4
Order By: Relevance
“…38 The majority of the studies utilized Grounded Theory 40 for data analysis. 25,28,[31][32][33][36][37][38][39] HRQOL issues for YASCC Domains and sub-domains of HRQOL that we identified in the present review are presented in Table 2. Consistent with the City of Hope framework [7][8][9] and the QOL-CS tool, 9 we found that physical, psychological, social, and spiritual issues are reported by YASCC.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…38 The majority of the studies utilized Grounded Theory 40 for data analysis. 25,28,[31][32][33][36][37][38][39] HRQOL issues for YASCC Domains and sub-domains of HRQOL that we identified in the present review are presented in Table 2. Consistent with the City of Hope framework [7][8][9] and the QOL-CS tool, 9 we found that physical, psychological, social, and spiritual issues are reported by YASCC.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The majority of the studies included both males and females. [24][25][26][27][28][29][30][31][32][33][34] Three studies did not indicate the gender distribution, [35][36][37] and the remaining two studies reported the inclusion of either all females 38 or all males. 39 The age of participants included in the studies ranged from 13 to 38 years old at the time of interview.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of specific character strengths may be seen as one such outcome. Peterson et al (2006:23) reported that adults who survived illness showed some character strengths to be relatively higher than those of healthy adults, and other researchers reported positive outcomes such as post-traumatic growth (Barakat et al 2005:413-419), thriving (Parry & Chesler 2005:1055 and flourishing (Phipps 2007(Phipps :1063 to emerge in the aftermath of childhood cancer. A similar pattern was thus expected in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Existing research on children and adolescent survivors suggest that there are many positive changes after successful cancer treatment (Kazak et al 1996:365) and that adolescents often report posttraumatic growth as reflected in positive changes in self, relationships with others and plans for the future (Barakat et al 2005:413). Some research even suggests that thriving (in a psychological sense) is a possible outcome of childhood cancer survival (Parry & Chesler 2005:1055. Recently, Phipps (2007Phipps ( :1063 argued that more attention should be given to positive emotional states in research with this population.…”
Section: Introductionmentioning
confidence: 99%